Family Assets and Liabilities in the Innovation Process. (November 2015) - Bennedsen, Morten; Foss, Nicolai
Innovation in family firms is often driven by family assets, valuable resources that are particularly prevalent in family firms. For example, they have particularly strong networks that can be deployed in an innovation context. These family assets can over time atrophy and stifle rather than stimulate innovation performance. However, family firms can fight this process by institutionalizing innovation within the family and the firm by means of family and corporate governance and through incentivizing key individuals in the innovation process.